Gender Attitudes And Behavioral Transformation Among Secondary Students: A Reflection Of Changing Nepalese Society - Tara Kesher Rawat (Journal of Contemporary Review, 2025)
This study explores gender attitudes and behavioural transformation among 315 secondary students from Gurbhakot, Bheriganga, and Lekbeshii Municipalities in Surkhet District, Nepal. The main goal was to examine how adolescents’ perceptions of gender equality are changing and how these changes reflect the broader transformation in Nepalese society. In this study descriptive cross-sectional study using a mixed-methods approach (quantitative and qualitative). Data were collected using a structured questionnaire covering gender attitudes, behavioural transformation, and influencing factors. Quantitative data were analysed using tables and graphs. Descriptive statistics (frequency, percentage) were used. Qualitative responses were analysed thematically. The findings reveal that 89.9% of respondents support equal access to education for both genders, and 91.8 % agreed that leadership roles should be equally accessible. Behavioural results show that 88.8 % of students often participate in co-educational activities and 73 % regularly challenge gender stereotypes. Parents (46.3%) and teachers (28.9 %) emerged as the strongest influencers. The results indicate that the youth in Surkhet are driving a significant shift toward gender equality, mirroring Nepal’s social modernization.